2014
DOI: 10.3923/pjbs.2014.720.724
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Infectious Bovine Rhinotracheitis in Dairy Animals with Reproductive Disorders in Uttar Pradesh, India

Abstract: Respiratory and reproductive disorders in dairy animals due to various etiological agents have led to significant economic losses to dairy industry. These losses are due to abortions, metritis, retention of placenta, repeat breeding, death of animals, loss of production and trade restrictions etc. The objectives of this cross-sectional study were to detect the seroprevalence of infectious bovine rhinotracheitis (IBR, BHV-1) in dairy animals of western parts of Uttar Pradesh, India. Anti BHV-1 antibodies were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
4
11
1
1
Order By: Relevance
“…Maximum seropositivity of IBR was found in animals between 3-4 years of age (Table 3) which was in agreement with Verma et al (2014) who reported that animals more than 2 years of age are more prone to IBR virus infection than younger animals. The possible reason might be production stress in this age group might lead to activation of latent infection and there were more chances of such animals get exposed to a natural infection.…”
Section: Resultssupporting
confidence: 90%
“…Maximum seropositivity of IBR was found in animals between 3-4 years of age (Table 3) which was in agreement with Verma et al (2014) who reported that animals more than 2 years of age are more prone to IBR virus infection than younger animals. The possible reason might be production stress in this age group might lead to activation of latent infection and there were more chances of such animals get exposed to a natural infection.…”
Section: Resultssupporting
confidence: 90%
“…[31] in Uttar Pradesh and Verma et al . [7] in Uttar Pradesh have also reported greater prevalence rate in cattle population than buffaloes.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our observation, Verma et al . [7] had observed more males to be seropositive than females in a study in Uttar Pradesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho and Bohac (1985) also pointed out the increased specificity and sensitivity of ELISA for detecting BoHV1 antibodies over other serological detection methods. The commercially available ELISA kits for the detection of antibodies against BoHV1 were used by many researchers (Ravishankar et al, 2012;Verma et al, 2014) and were found to be effective, rapid, and reliable in nature in comparison with the conventional assays which were time consuming and expensive.…”
Section: Results and Discussion Enzyme Linked Immunosorbent Assaymentioning
confidence: 99%